Mechanistic differences between HIV-1 and SIV nucleocapsid proteins and cross-species HIV-1 genomic RNA recognition. Issue 1 (December 2016) - Post, Klara; Olson, Erik; Naufer, M.; Gorelick, Robert; Rouzina, Ioulia; Williams, Mark; Musier-Forsyth, Karin; Levin, Judith
Abstract Background The nucleocapsid (NC) domain of HIV-1 Gag is responsible for specific recognition and packaging of genomic RNA (gRNA) into new viral particles. This occurs through specific interactions between the Gag NC domain and the Psi packaging signal in gRNA. In addition to this critical function, NC proteins are also nucleic acid (NA) chaperone proteins that facilitate NA rearrangements during reverse transcription. Although the interaction with Psi and chaperone activity of HIV-1 NC have been well characterized in vitro, little is known about simian immunodeficiency virus (SIV) NC. Non-human primates are frequently used as a platform to study retroviral infection in vivo; thus, it is important to understand underlying mechanistic differences between HIV-1 and SIV NC. Results Here, we characterize SIV NC chaperone activity for the first time. Only modest differences are observed in the ability of SIV NC to facilitate reactions that mimic the minus-strand annealing and transfer steps of reverse transcription relative to HIV-1 NC, with the latter displaying slightly higher strand transfer and annealing rates. Quantitative single molecule DNA stretching studies and dynamic light scattering experiments reveal that these differences are due to significantly increased DNA compaction energy and higher aggregation capability of HIV-1 NC relative to the SIV protein. Using salt-titration binding assays, we find that both proteins are strikingly similar in their ability to specifically interact with HIV-1 Psi RNA. In contrast, they do not demonstrate specific binding to an RNA derived from the putative SIV packaging signal. Conclusions Based on these studies, we conclude that (1) HIV-1 NC is a slightly more efficient NA chaperone protein than SIV NC, (2) mechanistic differences between the NA interactions of highly similar retroviral NC proteins are revealed by quantitative single molecule DNA stretching, and (3) SIV NC demonstrates cross-species recognition of the HIV-1 Psi RNA packaging signal.